Insights into the Decontamination of Cocaine-Positive Hair Samples. Issue 7 (7th October 2020) - Erne, Robert; Baumgartner, Markus R; Kraemer, Thomas
Abstract: A highly discussed step in hair sample preparation for forensic analytics is the applied decontamination. The here presented investigations aim to gain insight and give recommendations on how to conduct this decontamination for the analysis of cocaine consumption in hair. Key insights were gained from the investigation of cocaine consumer hair, which was artificially contaminated in a humid atmosphere with 13 C6 labelled cocaine and from cocaine powder contaminated hair. Several decontamination protocols were investigated, whereby the usage of a decontamination protocol consisting of multiple short repetitive washes allowed to visualize the wash out of ( 13 C6 -) cocaine. Multiple methanol washes proved to be an efficient and simple decontamination approach. Our findings showed that decontamination protocols can successfully wash out recent cocaine contaminations. They were observed to be rather quickly washed out, whereas cocaine from consumption or "older" cocaine contaminations were shown to eliminate both at a constant rate (from inner hair compartments). Thus, the usage of decontamination protocols to differentiate between consumption and contamination was shown to be limited. As contamination can happen any time at any level, only the application of elaborated decision trees, based on cocaine metabolite ratios and thresholds, can provide the distinction between consumption and contamination. Thus, the authors highly recommend the usage of such tools on all hair samples analyzed for cocaine consumption.